The mass impacts on chemosynthetic primary producers: potential implications on anammox communities and their consequences - Pérez Díaz, Noel; Velazco Vargas, Jorge Luis; Martín González, Osmel; Cárdenas Ortiz, Rolando Pedro; Martínez Frías, Jesús (My University, 2018)
The potential of a mass asteroid impact on Earth to disturb the chemosynthetic communities at global scale is discussed. Special emphasis is made on the potential influence on anammox communities and their implications in the nitrogen biogeochemical cycle. According to our preliminary estimates, anammox communities could be seriously affected as a consequence of global cooling and the large process of acidification usually associated with the occurrence of this kind of event. The scale of affectations could vary in a scenario like the Chicxulub as a function of the amount of soot, depth of the water column and the deposition rate for sulphates assumed in each case. The most severe affectations take place where the amount of soot and sulphates produced during the event is higher and the scale of time of settlements for sulphates is short, of the order of 10 h. In this extreme case, the activity of anammox is considerably reduced, a condition that may persist for several years after the impact. Furthermore, the impact of high levels of other chemical compounds like sulphates and nitrates associated with the occurrence of this kind of event are also discussed.
Keywords: Anammox; Chemosynthetic Communities; Chicxulub Impact; Nitrogen Cycle; Ocean Acidification; Earth and Planetary Astrophysics; Atmospheric and Oceanic Physics; Geophysics